Simplified Floating-Point Units for High Dynamic Range Image and Video Systems - Hormigo-Aguilar, Javier; Villalba-Moreno, Julio (My University, 2015)
The upcoming arrival of high dynamic range image and video applications to consumer electronics will force the utilization of floating-point numbers on them. This paper shows that introducing a slight modification on classical floating-point number systems, the implementation of those circuits can be highly improved. For a 16-bit numbers, by using the proposed format, the area and power consumption of a floating-point adder is reduced up to 70% whereas those parameters are maintained for the case of a multiplier.
Keywords: Arquitectura de ordenadores; Floating point; HUB format; High Dynamic Range; Optimization